Structural order and NIR reflective properties of perylene bisimide pigments: Experimental evidences from a combined multi-technique study. (August 2020) - Martini, Francesca; Minei, Pierpaolo; Lessi, Marco; Contiero, Luca; Borsacchi, Silvia; Ruggeri, Giacomo; Geppi, Marco; Bellina, Fabio; Pucci, Andrea
Abstract: This study reports the effect of the crystallinity degree and structural order of the supramolecular architectures of the perylene derivative Paliogen® Black L0086 (P-black) on the near-infrared (NIR) transparent, reflective and cooling characteristics of 75 μm thick acrylic coatings. Notably, XRD and solid-state NMR investigations revealed that on passing from the commercially available P-black C to the synthetic form P-black S, the average crystallinity passed from 20 to 48% flanked by a superior structural order that enhanced the mean crystallite width from 21.7 to 39.1 nm and maximum length from 1.5 μm to 6.5 μm, as evidenced by SEM micrographs. UV-VIS-NIR spectroscopic analyses of the coated surfaces confirmed the NIR transparent and reflective characteristics of the P-black pigment that was particularly relevant in the case of the pigment synthetic form. NIR reflectance enhancements from 25% to 50% were actually recorded on black surfaces on passing from the commercial to the synthetic form of the pigment dispersed into the acrylic coatings. This feature was reflected on the solar reflectance and the cooling effect, with values boosted from 9.9% to 18.2% and from 2.3 °C to 3.8 °C, respectively. Graphical abstract: Image 1 Highlights: Commercial and synthetic Paliogen black were utilized as cool organic pigments. Waterborne acrylic coatings were obtained on white and black substrates. XRD, ssNMR and SEM investigations evidenced the superior structural order of the synthetic pigment. SR measurements allowed to determine the cooling features of the prepared coatings.